Using Smart Apps Creator to Internalize Religious and Moral Values of Children - Yenti Juniarti; Waode Eti Hardiyanti; Icam Sutisna (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The problem is that there are still many teachers who have difficulty implementing religious and moral value development activities, and teachers have not been able to change IT-based learning. The purpose of this research is to equip teachers in making teaching materials using smart app creator applications, which can be accessed by everyone. The research method is Research Development (RD) Borg Gall design with 8 stages of research, 1) need assessment 2) planning 3) product development 4) initial field trial 5) product revision 6) main field trial 7) product revision 8) field test, 10) final product revision. The results of this study were obtained from media expert validation, namely very feasible, material expert validation very feasible, and learning expert validation very feasible). The results of the learning media assessment trial in the small group trial were 82.09% (very feasible) and in the large field trial, it was 88.89% (very worth it). Based on these results, the product is said to be suitable for use